43 Developing the simulation educators of the future: it takes nothing more than enthusiasm for simulation education. (17th November 2016) - Irshad, Sannaan; Kasfiki, E; Purva, M
Abstract : Background context: Training of simulation instructors is critical to developing high quality simulation programs. 1 Yet, a structured strategy on developing and sustaining simulation faculty is a challenge. 2 We describe a novel programme of developing faculty, which has helped increase our faculty base and sustain our simulation centre. Methodology: We created honorary posts for doctors in training working at Hull and East Yorkshire Hospitals NHS Trust with an interest in education and gave them the opportunity to learn on one-to-one basis from educators in simulation. These Associate Simulation Fellow posts were "in programme" placements therefore the doctors did not have to undergo "out of programme" formalities to undertake the post. A structured training process was provided by HILS; group sessions and one-to-one teaching in simulation based education, time with the technicians in HILS to become independent with controlling high fidelity simulators. They underwent a process of observing debrief, and providing supervised debrief. Associate simulation director, a previous Simulation Fellow at our organisation, supervised and mentored them. Results: 6 fellows were appointed in September 2015 following an interview process. All have completed a train the trainer course, delivered courses independently (with consultant supervision) and are contributing to research projects. All intend to continue their interests in simulation education. Each was able to contribute a minimum of 8 days to the scheme. Discussion: We have demonstrated that it is possible to create a pool of skilled simulation educators from the junior doctor workforce. Time constraints due to clinical commitments proved a challenge. However, the Fellows were resourceful and received good support from their educational supervisors to pursue their educational interest. We believe that this model can be extended to the rest of the workforce. References: Fanning R, Gaba D. The role of debriefing in Simulation-Based Learning. Simulation in Healthcare 2007;2 (2)115–125. McGaghie WC, Issenberg B, Petrusa E, Scalese R. A critical review of simulation-based medical education research. Med Educ 2010;44 (1)55–63.